Prevalence and Risk Factors for Peripheral Neuropathy in Chinese Patients With Gout - Guo, Kaifeng; Liang, Nan; Wu, Mian; Chen, Lihui; Chen, Haibing (Frontiers in Neurology, 2022)
Objective Peripheral neuropathies (PN) are a group of disorders that affect the peripheral nervous system. PN in gout has been scarcely described. This study is conducted to determine the prevalence and related risk factors of PN, as assessed by vibration perception threshold (VPT), in patients with gout. Methods A total of 442 patients were included in the cross-sectional study. The VPT values were measured using the Bio-Thesiometer sensory quantitative tester on each patient. VPT value of either limb higher than 15 V was considered abnormal, and is considered to have PN. Univariate and multivariate logistic regression models were used to identify risk factors for peripheral neuropathy in patients with gout. Results We included 442 gout patients, 97.5% males, 26.9% tophaceous gout, mean age 45.5±15.2 years, 7.4±4.6 years of disease duration. The prevalence of peripheral neuropathy in patients with gout was 11.1%. Patients in the abnormal VPT group were older, had a longer gout duration, and had significantly higher levels of waist circumference, waist/hip ratio, systolic blood pressure (SBP), erythrocyte sedimentation rate (ESR), as compared to patients in the normal vibration group (all P-values < 0.05). Univariate logistic regression analysis demonstrated that there was a significant association between abnormal VPT and age, duration of gout, SBP, C-reactive protein, ESR, presence of tophi and eGFR in all subjects (P<0.05). Multivariate logistic regression analysis indicated that, age (odds ratio, 1.094) and presence of tophi (odds ratio, 1.048) were independent risk factors for peripheral neuropathy in patients with gout. Conclusions The abnormal VPT was significantly correlated with age and presence of tophi in patients with gout, and the VPT levelmay be useful as a screening tool for PN assessment in gout.